Effect of pyrolysis condition on the adsorption mechanism of lead, cadmium and copper on tobacco stem biochar. (20th June 2018) - Zhou, Zhi; Xu, Zhihui; Feng, Qiuju; Yao, Denghui; Yu, Jingang; Wang, Desheng; Lv, Shuangqing; Liu, Yifei; Zhou, Nan; Zhong, Mei-e
Abstract: To promote the application of biochar in environmental pollution decontamination especially the heavy metals amendment, the relationship between the adsorption mechanism and biochar pyrolysis conditions was investigated. Tobacco stem was pyrolyzed at 300–700 °C for various residence time of 2 h, 4 h and 6 h. The adsorption of lead, cadmium and copper in single solute was then analyzed for as-obtained biochars. The change of the crystal structures, the related functional groups, and the exchanged cations were determined to reveal the effect of pyrolysis conditions on the adsorption mechanisms of these three heavy metals. The change of crystal structure confirmed that precipitation was the main mechanism of lead adsorption and that the tobacco stem biochar obtained at 700 °C for around 2 h was excellent adsorbent for lead clearance, since high temperature pyrolysis could promote the formation of carbonates but they would be decomposed under long-time exposure. The alteration of surface functional groups and exchanged cations of both original and demineralized biochars followed an affinity order of Cu(II)>Cd(II)>Pb(II) to oxygen functional groups. The surface complexation should be the primary mechanism of copper adsorption. Thus, the tobacco stem biochars pyrolyzed at 400 °C for 4 h could be effective adsorbents for copper amendment. Despite of the important role of precipitation in its removal, cadmium favores the cation-π interaction best, and the biochars derived from tobacco stem at 700 °C for the residence time of 4–6 h are good adsorbents for cadmium decontamination. Graphical abstract: Image 1 Highlights: Relationship between adsorption mechanisms and pyrolysis conditions was studied. Main adsorption mechanism of Pb, Cd, Cu is precipitation, π interaction, surface complexation. Higher temperature can benefit the formation of aromatic carbon and minerals. Longer residence time has positive effect on the decrease of OFGs and minerals. Efficient lead, cadmium and copper removal by tobacco stem biochar.